Effects of cornering conditions on the aerodynamic characteristics of a high-performance vehicle and its rear wing - Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Brighton, James (American Institute of Physics (AIP), 2024)
This study investigates the aerodynamic behavior of a high-performance vehicle and the interaction with its rear wing in straight-line and steady-state cornering conditions. Analyses are performed with Reynolds-averaged Navier–Stokes based computational fluid dynamics simulations using a moving reference frame and overset mesh technique, validated against moving ground wind tunnel experiments. The results indicate a significant 20% decrease in downforce and 35% increase in drag compared to straight-line conditions at the smallest considered corner radius of 2.9 car-lengths. Downforce losses primarily stem from performance deficits on the underbody and rear wing, alongside elevated upper body lift. Drag penalties mainly result from additional pressure drag induced by a recirculation wake vortex generated behind the vehicle's inboard side. The vehicle's lateral pressure distribution is also affected, introducing a centripetal force that increases with smaller corner radii. Additionally, analyses of the rear wing reveal alternations of its aerodynamic characteristics in cornering, particularly impacting vortical flow and suction on the lower surface. Throughout the operating conditions, the rear wing's individual downforce contribution falls off beyond its stall angle. At higher angles of attack, the rear wing primarily generates downforce by pressurizing the vehicle's upper surfaces, but its interaction with the near-wake leads to a substantially increased pressure drag. Overall, these findings provide crucial insights into the intricate aerodynamic interactions of high-performance vehicles in diverse operating conditions as well as form an essential foundation for future research on static and active aerodynamic designs in the pursuit to optimize vehicle performance in dynamic driving conditions.
Keywords: Vehicle technology; Computational fluid dynamics; Aerodynamics; Flow simulations